2009
DOI: 10.1002/jsfa.3528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of incorporated amaranth albumins on the functional properties of wheat dough

Abstract: BACKGROUND: Recent developments in micro-scale testing methodology and in methods modelling the effects of native forms of constituents by in vitro methods have provided a new approach to study the impact of added foreign proteins on dough end-use quality. Amaranth (Amaranthus) is a member of the pseudo-cereal family, whose storage proteins have superior nutritional quality due to their essential amino acid composition. The aim of this project was to study the effects of the incorporated amaranth albumin prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 60 publications
3
25
0
1
Order By: Relevance
“…The increase of DDT and ST indicated that surimi addition produced more stable dough. A similar trend was reported that amaranth proteins modified the stability-related mixing parameters (DDT and ST) of dough (Oszvald et al, 2009). …”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The increase of DDT and ST indicated that surimi addition produced more stable dough. A similar trend was reported that amaranth proteins modified the stability-related mixing parameters (DDT and ST) of dough (Oszvald et al, 2009). …”
Section: Resultssupporting
confidence: 85%
“…A network-like structure could be created with surimi protein and gluten, which could strengthen the dough structure during mixing. Oszvald et al, (2009) found that amaranth albumin proteins are capable of interacting with gluten proteins in wheat flour, improving dough strength and stability. Similar trend was also observed in the study of the blended wheat flour and soy flour (Singh and Mohamed, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The alveogram results provided by the authors suggested and baking test approved the improvement of the dough properties and bread crumb characteristics when albumin isolates were added. Similarly, Oszvald et al (2009) reported the beneficial effects of amaranth albumin to wheat supplementation even in concentrations from 1% to 5% relative to the protein content of wheat (i.e. about one tenth of the protein used in the aforementioned study).…”
Section: Resultsmentioning
confidence: 72%
“…Among the studies on composite flours containing amaranth only a few deal with the rheological characteristics of the dough (Lorenz 1981;Breene 1991;Tosi et al 2002;Silva-Sánches 2004;Sindhuja et al 2005;Oszvald et al 2009). However, these properties are important for the prediction of the dough behaviour during mechanical handling in breadmaking as they affect the quality of the resulting loaf.…”
mentioning
confidence: 99%
“…El amaranto contiene alto valor proteico, fibras y riqueza en minerales (Fe, Ca y Zn); estos atributos lo convierten en una buena alternativa como ingrediente para pastas y contribuyen a promover la variedad culinaria y valoración de los granos étnicos de Latinoamérica [5][6][7] . Además, el reemplazo del trigo por amaranto en un 20 a 25% tiene un aporte de 14 a 17g de proteína en 100g de pasta 8 .…”
Section: Introductionunclassified